ABIUS AS A NEW CATEGORY IN FAMILY PSYCHOLOGY - Семиченко, B.; Дубчак, O. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2019)
The term "abuja" relatively recently began to be used in domestic psychology, although abroad the feasibility of its allocation as an independent psychological phenomenon is proven. It should be noted that our experience (conversations, observation, experience of psycho-counseling work) much earlier than the concept of an abuse was included in the scientific thesaurus, led us to believe in the need to consider the specific features of family relations when the position of one of the family members is different special discomfort. This mainly concerned the relationship between parents and children, men and women. Almost no attention was paid to the relationship between adult children and older generations. The purpose of our article was to theoretically investigate the concept of abjuse, abusive relationships, in particular between middle and older generations. Summarizing the manifestations of such relationships, develop a questionnaire for identifying signs of autism, which manifests itself in relation to the older generation. By research methods we chose observation and conversation with representatives of the older generation in families, which in the future will give grounds for creating a questionnaire for identifying signs of abusive relationships and abusers. The conducted theoretical study provides the basis for the following conclusions: psychological abruption in the family for the elderly - a fairly widespread phenomenon. It is not noticeable for its participants in the person who acts as a victim, formed racks complexes: a complex of inferiority and a complex of trained helplessness. In case of exacerbation of situations, excessively rigid psychological pressure is lost faith in a better future, a feeling that everything is good in the past. The dominant perception of the world is the desire to disappear, at least for a time to leave the family circle, or even die at all. Characteristically, this often occurs against the backdrop of maintaining a generally positive attitude towards loved ones. Therefore, the situation of a victim's life in such conditions can be compared to a swing on which the axis of human life is constantly shaking. This is a very unfavorable situation in which psychosomatics afflicts. At the same time, the traditional advice for family psychotherapists - to break the relationship with the abuser - often can not simply be fulfilled, since elderly people often really need help from other family members, and family manipulators simply do not realize the presence of some problem in relationships, the need see something in family relationships. Therefore, the problem of overcoming traumatic relationships between generations in the family requires special attention of specialists.